AB0941 Systematic Literature Review of Ultrasound in Large Vessel Vasculitis for Establishing Omeract Definitions. (15th July 2016) - Duftner, C.; Dejaco, C.; Iagnocco, A.; Schmidt, W.A.
Abstract : Background: Ultrasound (US) is increasingly used for the diagnosis of large vessel vasculitis (LVV), as this imaging technique enables the visualization of the inflammatory vessel wall swelling. A consensus about the definition of US lesions for diagnosis of LVV has not yet been accomplished. Objectives: 1) To identify definitions of US lesions in LVV; 2) to evaluate the role of US in monitoring disease response; and 3) to assess the value of identified US lesions for diagnosis of LVV. Methods: A systematic literature search was conducted in PubMed, Embase and the Cochrane Library (till 23rd November 2014). Research articles enrolling at least 20 patients with suspected cranial giant cell arteritis (GCA) or large-vessel GCA (LV-GCA), Takayasu arteritis (TAK), published in English or German were selected. The study design, subjects, methods, imaging protocols and diagnostic values were evaluated, as well as the US definitions of vasculitis. The quality of the included studies was assessed by the QUADAS2 tool. Results: Of 2960 articles identified, 34 studies were included in the review for the extraction of definitions of vasculitis in US. Thirty-two reports addressed the role of US in diagnosis of cranial GCA, whereas only 6 studies evaluated US in the settings of LV-GCA. The role of US in disease monitoring was evaluated in 11 articles on cranial GCA and in 2 articles on LV-GCA. No studies assessing the role of US in TAK fulfilled the inclusion criteria. Most studies investigated the value of the "halo sign" (32 articles), whereas "compression sign", "stenosis", "occlusion" or "decreased vessel wall pulsation" as signs of vasculitis were addressed in 1, 22, 19, and 1 paper(s), respectively. Conclusions: US is a valuable diagnostic tool in patients with suspected GCA. In this systematic literature review we identified "halo sign", "stenosis", "occlusion", "compression sign" and a "decreased vessel wall pulsation" as possible key US lesions for vasculitis. Based on these results future research on the role of US in LVV is now being performed by the OMERACT US group. Disclosure of Interest: None declared